Mekanisme Pertahanan Ego dalam Novel Rapijali 2: Menjadi karya Dee Lestari: Kajian Psikoanalisis Sigmund Freud - Fadila Pratiwi; Yenni Hayati (Persona: Kajian Bahasa dan Sastra, 2022)
This study aims to describe the form of the ego defense mechanism in the novel Rapijali 2: Menjadi by Dee Lestari. This type of research is literary research using descriptive method. The research data are in the form of words, phrases, clauses, sentences, narration from the narrator, character utterances, and actions of characters related to the ego defense mechanism in the novel Rapjali 2: Being by Dee Lestari. The data collection techniques in this study were as follows: (1) conducting a literature study, (2) reading and understanding the novel, (3) marking the part of the novel that indicated the ego defense mechanism, (4) recording data related to the ego defense mechanism. , (5) identify the main characters and additional characters in the novel, and (6) take an inventory of the data found in the novel. There are four data analysis techniques in this study, namely: analyzing data on forms of ego defense mechanisms, interpreting data on forms of ego defense mechanisms, making conclusions about research results, and reporting research results. The research results obtained are: the form of ego defense mechanism in the novel Rapijali 2: Menjadi by Dee Lestari which is divided into, (a) repression, (b) projection, (c) diversion, (d) rationalization, (e) reaction formation, ( f) regression, and (g) aggression and apathy. Based on these findings, it turns out that the ego defense mechanism is a form of self-defense mechanism to overcome anxiety which is often used by characters in novels.